Anaesthetic and Critical Care Management of Thoracic Injuries. Issue 3 (1st September 2010) - Round, JA; Mellor, Adrian
Abstract : Thoracic wounding has been a relatively common presentation of military wounds throughout modern conflict. When civilian casualties are included the incidence has remained constant at around 10%, although the frequency and severity of wounds to combatants has been altered by modern body armour. Whilst thoracic injury has a high initial mortality on the battlefield, those surviving to reach hospital frequently have injuries that only require simple management. In addition to penetrating ballistic injury, blunt chest trauma frequently occurs on operations as a result of road traffic collisions or tertiary blast injury. The physiological impact of thoracic wounds, however, is often great and survivors often require intensive care management and, where available, complex strategies to ensure oxygenation and carbon dioxide removal. This review examines the incidence and patterns of thoracic trauma and looks at therapeutic options for managing these complex cases.